2016
DOI: 10.17113/ftb.54.04.16.4623
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Pumpkin Oil Recovery by Using Aqueous Enzymatic Extraction and Comparison of the Quality of the Obtained Oil with the Quality of Cold-Pressed Oil

Abstract: The study was carried out to optimize pumpkin oil recovery in the process of aqueous extraction preceded by enzymatic maceration of seeds, as well as to compare the quality of the obtained oil to the quality of cold-pressed pumpkin seed oil. Hydrated pulp of hulless pumpkin seeds was macerated using a 2% (by mass) cocktail of commercial pectinolytic, cellulolytic and proteolytic preparations (Rohapect UF, Rohament CL and Colorase 7089). The optimization procedure utilized response surface methodology based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 36 publications
5
30
0
1
Order By: Relevance
“…The sterol content was affected mostly by genotype impact (42.9-83.8% of the determined variation), followed by the significant impact of the year (only one exception for ∆7,22,25-stigmastatrienol) and interaction of these traits (Table 2). The content and composition of sterols determined in the current study were in range of 225-343 mg/100 g reported in the previous studies [49][50][51]. Significantly more abundant in sterols are, for example, rapeseed oil (ca.…”
Section: Sterols Content and Compositionsupporting
confidence: 54%
See 1 more Smart Citation
“…The sterol content was affected mostly by genotype impact (42.9-83.8% of the determined variation), followed by the significant impact of the year (only one exception for ∆7,22,25-stigmastatrienol) and interaction of these traits (Table 2). The content and composition of sterols determined in the current study were in range of 225-343 mg/100 g reported in the previous studies [49][50][51]. Significantly more abundant in sterols are, for example, rapeseed oil (ca.…”
Section: Sterols Content and Compositionsupporting
confidence: 54%
“…Although sterol content in pumpkin seed oil is not distinctive, this oil is unique considering its sterol composition. β-sitosterol prevails in the majority of typical plant oils [53], while ∆7-sterols dominate in pumpkin oil, accounting for at least 91% [14,50]. A lower level of these ∆7-sterols detected in commercial pumpkin oil can indicate its adulteration [54].…”
Section: Sterols Content and Compositionmentioning
confidence: 99%
“…Tradicionalmente el aceite de palta solía obtenerse triturando la pulpa en presencia de agua, posteriormente se procedía a calentar y separar el aceite sobrenadante; sin embargo, por las características del mesocarpio, algunos métodos de extracción requieren una reducción del contenido de humedad, lo que permite inactivar las actividades enzimáticas y microbianas, aumentando su vida útil (Dorantes et al, 2004). Esto permite el uso del prensado hidráulico, el prensado por expeller y la extracción con solvente; aunque sólo los métodos mecánicos, como el prensado, permiten obtener aceite de uso directo (Konopka et al, 2016), el método Soxhlet utiliza hexano para la extracción del aceite por solvente, por su fácil recuperación (Satriana et al, 2019). Desafortunadamente el hexano es un solvente muy cuestionado desde el punto de vista toxicológico y ambiental (Fernández et al, 2018).…”
Section: Introductionunclassified
“…During the AEE procedure, cellular structure and non‐soluble proteins around the oil micelles are hydrolyzed by carbohydrases and proteases, respectively, and the oil is released into the aqueous media . Enzymatic pretreatment may be considered as a basic operation for AEE, but it results in a disadvantage due to relatively high cost of enzymes . A known character of krill is the very efficient digestion system, which is based on a combination of enzymes, especially trypsin‐like proteinases .…”
Section: Introductionmentioning
confidence: 99%
“…[7] Enzymatic pretreatment may be considered as a basic operation for AEE, but it results in a disadvantage due to relatively high cost of enzymes. [8] A known character of krill is the very efficient digestion system, which is based on a combination of enzymes, especially trypsin-like proteinases. [9] The degradation efficiency of the trypsin-like proteinases is found to be %12 times higher than bovine trypsin at 37 C. [9] In our previous work, the strong endogenous proteases of krill were efficiently utilized to hydrolyze kill proteins, [1] and it was found that the oils were released from krill organisms during autolysis of krill.…”
Section: Introductionmentioning
confidence: 99%